Renal cell carcinoma of a horseshoe kidney mistaken for ovarian malignancy - Adhikari, S; Rana, A; Gurung, G; Adhikari, R; Vaidya, P; Joshi, B (Journal of Institute of Medicine Nepal, 2007)
Background: Heterogonous complex mass suspected to be ovarian tumour preoperatively in the vicinity of both low lying kidneys in close approximation to enlarged lymph node by trans abdominal ultrasound was found to be renal cell carcinoma arising from horseshoe kidney. Case report: A rare presentation, is described herewith in a multiparous (P6), 57 year old post menopausal lady who suffered from pyrexia for 2 months and mass abdomen for 3 years. Key words: horseshoe kidney, ovarian tumor, renal cell carcinoma. The full text of this paper is available at Journal of Institute of Medicine website